Rationale for anti-GITR cancer immunotherapy. (November 2016) - Knee, Deborah A.; Hewes, Becker; Brogdon, Jennifer L.
Abstract: Over the past decade, our understanding of cancer immunotherapy has evolved from assessing peripheral responses in the blood to monitoring changes in the tumour microenvironment. Both preclinical and clinical experience has taught us that modulation of the tumour microenvironment has significant implications to generating robust antitumour immunity. Clinical benefit has been well documented to correlate with a tumour microenvironment that contains a dense infiltration of CD8 + CD45RO + T effectors and a high ratio of CD8 + T cells to FoxP3 + regulatory T cells (Tregs). In preclinical tumour models, modulation of the Glucocorticoid induced TNF receptor (GITR)/GITR ligand (GITRL) axis suggests this pathway may provide the desired biological outcome of inhibiting Treg function while activating CD8 + T effector cells. This review will focus on the scientific rationale and considerations for the therapeutic targeting of GITR for cancer immunotherapy and will discuss possible combination strategies to enhance clinical benefit.